Retrospective Comparison of Minimally Invasive and Open Monosegmental Lumbar Fusion, and Impact of Virtual Reality on Surgical Planning and Strategy - Zawy Alsofy, Samer; Nakamura, Makoto; Ewelt, Christian; Kafchitsas, Konstantinos; Lewitz, Marc; Schipmann, Stephanie; Suero Molina, Eric; Santacroce, Antonio; Stroop, Ralf (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Spinal fusion for symptomatic lumbar spondylolisthesis can be accomplished using an open or minimally invasive surgical (MIS) technique. Evaluation of segmental spondylolisthesis and instabilities and review of their therapies are inseparably connected with lumbar tomographic imaging. We analyzed a cohort of patients who underwent MIS or open monosegmental dorsal fusion and compared surgical outcomes along with complication rates. We furthermore evaluated the influence of virtual reality (VR) visualization on surgical planning in lumbar fusion.Material and Methods Patient files were retrospectively analyzed regarding patient- and disease-related data, operative performance, surgical outcomes, and perioperative surgical complications. Preoperative computed tomography (CT) and magnetic resonance imaging (MRI) scans were retrospectively visualized via VR software. A questionnaire evaluated the influence of three-dimensional (3D) VR images versus two-dimensional CT and MRI scans on therapy planning, fusion method, and surgical technique and procedure.Results Overall, 171 patients were included (MIS/open: 90/81). MIS was associated with less blood loss, shorter surgery time and hospital stay, lower complication rates, equivalent long-term patient-reported outcomes, but lower fusion rates and higher late reoperation rates than open surgery. Image presentation using VR significantly influenced the recommended surgical therapies (decompression only/decompression and fusion; p = 0.02), had no significant influence on the recommended fusion method (rigid/dynamic/stand-alone; p = 0.77), and, in cases of rigid fusion, a significant influence on the recommended technique (MIS/open; p = 0.03) and fusion procedure (p = 0.02).Conclusion In patients with monosegmental degenerative or isthmic spondylolisthesis, MIS fusion was advantageous concerning perioperative complication rates and perioperative surgical outcomes, but disadvantageous regarding fusion and reoperation rates compared to open fusion. 3D-VR-based analysis of sectional images significantly influenced the recommended surgical planning.
Keywords: lumbar spondylolisthesis; minimally invasive fusion; monosegmental instability; open fusion; virtual reality